2024
DOI: 10.1037/trm0000248
|View full text |Cite
|
Sign up to set email alerts
|

The importance of maintaining medical professionalism while experiencing vicarious trauma when working with human trafficking victims.

Abstract: Providing health care services to human trafficking victims may negatively impact the psychological wellness and decision-making process of health care providers, especially mental health providers. This article highlights John Gregory's concept of medical professionalism and discusses how the fundamental virtues, integrity, compassion, self-sacrifice, and self-effacement can guide health care providers in managing their work with trafficked patients. Recommendations are provided to health care providers, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Participant 1 defines the difference between being a “warm fire” for someone, as opposed to taking on their trauma (Cuartero & Campos-Vidal, 2019), and furthermore recognizes the importance of acknowledging their work’s positive impact on their clients to fuel compassion satisfaction against compassion fatigue (Figley, 1995; Ramirez et al, 2020):My therapist calls it being a warm fire. And it’s just like, being with the person…I can just be a warm presence, so that that person doesn’t have to go through it alone…and we’re able to, erm, see the difference and act to change it.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Participant 1 defines the difference between being a “warm fire” for someone, as opposed to taking on their trauma (Cuartero & Campos-Vidal, 2019), and furthermore recognizes the importance of acknowledging their work’s positive impact on their clients to fuel compassion satisfaction against compassion fatigue (Figley, 1995; Ramirez et al, 2020):My therapist calls it being a warm fire. And it’s just like, being with the person…I can just be a warm presence, so that that person doesn’t have to go through it alone…and we’re able to, erm, see the difference and act to change it.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research has defined vicarious trauma and burnout, or compassion fatigue, as a ubiquitous occurrence amongst mental health professionals who face a high level of professional contact with traumatized clients generally (Benuto et al, 2018;Bride, 2007;Fahy, 2007) and with survivors of human trafficking specifically (Ramirez et al, 2020). A study by Ting et al (2011) found that social workers experienced high levels of perceived stress initially after being confronted with client suicidal behaviour (CSB) that had the potential to develop into long-term perceived stress if not processed properly.…”
Section: Burnout and Vicarious Traumamentioning
confidence: 99%
See 3 more Smart Citations